Art therapy in psychosocial intervention for alcohol use disorder: a case study - Dinçelli, Buket Canan; Maçkalı, Zeynep; Eracar, Nevin; Bilici, Rabia (Journal of Dependence, 2025)
This case study aims to show how art therapy, as a part of psychosocial intervention in the treatment of alcohol use disorder, can help the patient increase their self-expression skills and symbolization skills, develop appropriate coping methods, and increase one’s functioning. The client was diagnosed with alcohol use disorder and has been in remission for 14 months, had 42 (+1) sessions during the 15-month process using art therapy. In each session, various art therapy exercises were carried out from different art modalities such as painting, literature, music, dance/movement, taking into account the client’s situation and needs. In this article, eight sessions, which are thought to reflect the psychological conflict and progress experienced by the client are included. It is seen that art therapy techniques experienced by individuals with alcohol use disorder can be helpful in diagnosis and evaluation at the beginning. Besides these techniques can have positive effects on increasing the ability of self-expression and symbolization, developing appropriate coping skills and increasing psychosocial functioning by enabling the client to establish causal relationships between symptoms, complaints, and life cycles. It is suggested that such programs might be included in psychosocial interventions to prevent relapses of individuals suffering from addiction and to strengthen their psychological resilience.